Comparison of Some Estimators under the Pitman's Closeness Criterion in Linear Regression Model. (23rd April 2014) - Wu, Jibo
Abstract : Batah et al. (2009) combined the unbiased ridge estimator and principal components regression estimator and introduced the modified r - k class estimator. They also showed that the modified r - k class estimator is superior to the ordinary least squares estimator and principal components regression estimator in the mean squared error matrix. In this paper, firstly, we will give a new method to obtain the modified r - k class estimator; secondly, we will discuss its properties in some detail, comparing the modified r - k class estimator to the ordinary least squares estimator and principal components regression estimator under the Pitman closeness criterion. A numerical example and a simulation study are given to illustrate our findings.